Matematyka
jan632
2017-09-24 08:54:15
Wyrażenie [latex] frac{6x^2-6y^2}{x^2+2xy+y^2}[/latex] jest równe : A. [latex]frac{3}{xy}[/latex] B.[latex]-3 frac{y}{x} [/latex] C.[latex]6 frac{x+y}{x-y} [/latex] D.[latex]6 frac{x-y}{x+y} [/latex]
Odpowiedź
513038562
2017-09-24 10:09:13

(6x²-6y²) :(x²+2xy+y²)= [6(x²-y²)]: [(x+y)(x+y)]= [6(x+y)(x-y)] : [(x+y)(x+y)]= = [6 (x-y)] : (x+y) odp. D

kasia1121
2017-09-24 10:10:28

Korzystamy ze wzorów skróconego mnożenia: [latex]a^{2}-b^{2}=(a-b)(a+b)\a^{2}+2ab+b^{2}=(a+b)^{2}[/latex] [latex]frac{6x^{2}-6y^{2}}{x^{2}+2xy+y^{2}}=frac{6(x^{2}-y^{2})}{(x+y)^{2}}=frac{6(x-y)(x+y)}{(x+y)(x+y)}=frac{6(x-y)}{x+y}=6frac{x-y}{x+y}[/latex] Odpowiedź: D

Dodaj swoją odpowiedź